ANALISIS METAKOGNISI SISWA SMA KARUNA DIPA PALU DALAM MEMECAHKAN MASALAH BARISAN DAN DERET ARITMETIKA DITINJAU DARI KEMAMPUAN MATEMATIKA: Analysis of Metacognition Students of SMA Karuna Dipa Palu in Solving Arithmetic Sequences and Series Problems Reviewed from Mathematical Ability - Islam, Fahrul; Lefrida, Rita; Karniman, Tegoeh S.; Murdiana, I Nyoman (Universitas Tadulako, 2024)
This study aims to metacognition of students SMA Karuna Dipa Palu with high, medium and low mathematical abilities in solving problems of arithmetic sequences and series in terms of mathematical abilities. This type of research is descriptive with a qualitative approach. This research was conducted in class XI IPA at SMA Karuna Dipa Palu in the 2023/2024 academic year with one student each with high, medium and low mathematics abilities. Data collection techniques use written assignments and interviews. This research uses two instruments, namely the main instrument, namely the researcher himself, and supporting instruments, namely written assignment sheets and interview guidelines. Data analysis is carried out through data condensation, data presentation, drawing conclusions. The results of the research show that: (1) The metacognition of students with high mathematical abilities in solving problems by Polya fulfills all indicators of understanding the problem well even without writing down what is known and asked, planning problem solving, implementing the problem solving plan, and checking the results of problem solving again with Good; (2) the metacognition of students with moderate mathematical abilities in solving problems by Polya meets the indicators very satisfactorily, written in detail; (3) the metacognition of students with low mathematical abilities in solving problems by Polya is not good enough in all indicators of understanding the problem, planning problem solving, carrying out problem solving, and checking the results of problem solving.